STRENGTHENING THE CAPABILITY OF STUDENTS IN DEVELOPING ENVIRONMENTAL ETHICS-BASED COVID-19 PREVENTION SYSTEMS IN Pesantren THROUGH ASSISTANCE PROGRAMSTRENGTHENING THE CAPABILITY OF STUDENTS IN DEVELOPING ENVIRONMENTAL ETHICS-BASED COVID-19 PREVENTION SYST - Siti seituni Acik; Ahmad Hafas Rasyidi; Lisma Dian Kartika Sari; Tri Astindari; Sahwari (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The ethical behavior of the santri environment and the pesantren community is still low. This has the potential to cause Islamic boarding schools to become new clusters for the spread of Covid-19. The low environmental ethical behavior of the Salafiyah Dawuhan Islamic Boarding School students is a problem caused by 3 things, namely: 1) there is no formulation of environmental ethics based on Islamic values ??so that it can be internalized into ready-to-use regulations as guidelines. behavior in the pesantren environment. 2) Awareness of students about the importance of environmental and health ethics is still low because: a) the majority of students believe that ethics in life is the most important thing in ethics to fellow human beings, while ethics to the surrounding environment are considered unimportant to be implemented. b) The students have not realized the importance of environmental ethics for life in this world and in the hereafter. c) The students do not have a good enough understanding of Covid-19 and how to prevent it related to environmental ethical behavior. 3) Islamic boarding schools do not yet have a behavioral regulation system that is oriented towards environmental ethics, especially in the form of written rules and prohibitions and sanctions for those who violate them, as well as an organizational structure that supports their enforcement. The quantitative method and stages carried out in community service activities are by holding a Forum Group Discussion (FGD) to explore Islamic values ??that can be used as a formulation of environmental ethics and a bulwark to prevent the transmission of Covid-19. The result is a formulation of environmental ethics based on Islamic values ??that can be internalized into the discipline of students. By producing workshop activities, it will have an impact on: a) increasing the ability of students in compiling the Covid-19 prevention behavior regulation system that is oriented towards environmental ethics. b) Compilation of rules for students based on environmental ethics which will be displayed on the pesantren website and available bulletin boards. c) The organizational structure of the Environmental Ethics Violation Control Task Force and the Covid-19 Prevention Protocol in Islamic Boarding Schools. b) Compilation of rules for students based on environmental ethics which will be displayed on the pesantren website and available bulletin boards. c) The organizational structure of the Environmental Ethics Violation Control Task Force and the Covid-19 Prevention Protocol in Islamic Boarding Schools. b) Compilation of rules for students based on environmental ethics which will be displayed on the pesantren website and available bulletin boards. c) The organizational structure of the Environmental Ethics Violation Control Task Force and the Covid-19 Prevention Protocol in Islamic Boarding Schools. Keywords: covid 19, students, boarding schools